The impact of selected input and output factors on measuring research efficiency of university research fields: insights from a purpose-, field-, and method-specific perspective - Heinz Ahn; Marcel Clermont; Julia Langner (Journal of Business Economics, 2022)
The measurement of universities' efficiency is gaining importance due to the increasing competitive pressure. As the results of such a measurement depend especially on the included input and output factors, it is essential to select them carefully to generate valid results. Against this background, we analyze the impact of including selected input and output factors on measuring the research efficiency of university research fields by applying best-practice frontier benchmarking methods. Based on a standard scenario, we consider the additional inclusion of expenditures, research grants, and bibliometric indicators. In doing so, we take account of different research fields as well as methods and purposes of measuring efficiency. Regarding the latter aspect, we distinguish between the computed efficiency degrees and the resulting ranking. We observe that the additional input and output factors have a quite heterogeneous impact on the respective evaluation criteria. The corresponding findings are relatively robust with respect to the research fields and methods considered. Our results provide guidance for evaluators as well as university and political decision-makers.
Keywords: 650; Research efficiency of university research fields; Influence of input and output factors; Expenditures; Research grants; Bibliometric indicators; Best-practice frontier benchmarking methods